Pelatihan Senam Lansia Untuk Meningkatkan Kesehatan Fisik Dan Kualitas Hidup Warga Panti Werdha - Rahmat Pannyiwi; Tata Mahyuvi; Adisty Dwi Treasa (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The aging process causes a decline in physiological, psychological, and social functions that affect the physical health and quality of life of older adults. Regular physical activity, such as through exercise for older adults, has been proven to increase muscle strength, flexibility, balance, and prevent degenerative diseases. This Community Service activity aims to improve the physical health and quality of life of nursing home residents through exercise training for older adults. The methods included counseling, demonstrations, joint practice, and pre-test and post-test evaluations. The results showed a significant increase in physical fitness, balance, flexibility, muscle strength, and the participation of the elderly in physical activities. Senior gymnastics training is recommended as a routine program to improve the health and quality of life of the elderly.